Falling behind a jet ski: A sad end to a pleasure ride. (January 2016) - Atlas, Ilan; Jerdev, Michael; Younis, Johnny S; Khateeb, Mohanna; Shlomo, Izhar B; Nicola, Adeeb
We report three cases of serious combined rectovaginal injuries, from a forceful waterjet after falling backwards with legs abducted from the back of a jet ski. In all cases, the passengers were unaware of this risk and did not wear protective clothing. In one case, massive fecal spillage to the lower and upper retropritoneum led to death within 33 h, despite laparotomy, colostomy and retroperitoneal lavage. We recommend increasing the awareness of jet ski drivers and passengers to this particular danger, using protective suits and enforcement of adequate boating regulation by the local authorities. Hospitals located near recreational boating amenities must maintain higher alertness and capability of dealing with such particular serious and complicated injuries.